2022
DOI: 10.3389/fpsyt.2022.833394
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19 Pandemic on Individuals With Pre-existing Obsessive-Compulsive Disorder in the State of Qatar: An Exploratory Cross-Sectional Study

Abstract: BackgroundPublished evidence about the impact of the COVID-19 pandemic on Obsessive-Compulsive Disorder (OCD) is conflicting. Most studies suggest an increase in the severity of OCD in people with pre-existing OCD, whereas some do not.AimGiven the conflicting evidence globally and lack of data from the Arab world, we aimed to explore the impact of the pandemic on obsessive-compulsive symptoms in adults with pre-existing OCD.MethodsA telephonic questionnaire-based cross-sectional study among adults with pre-exi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…The chronicity of symptoms might be an important factor. For example, another cross-sectional study in Qatar showed that those with a shorter illness duration (<10 years) experienced a larger deterioration of OCSs ( Siddiqui et al, 2022 ). One can speculate that people with a more chronic symptomatology are less prone to external changes, are better embedded in a treatment, or are on stable psychopharmacological medication.…”
Section: Discussionmentioning
confidence: 99%
“…The chronicity of symptoms might be an important factor. For example, another cross-sectional study in Qatar showed that those with a shorter illness duration (<10 years) experienced a larger deterioration of OCSs ( Siddiqui et al, 2022 ). One can speculate that people with a more chronic symptomatology are less prone to external changes, are better embedded in a treatment, or are on stable psychopharmacological medication.…”
Section: Discussionmentioning
confidence: 99%